Novel Receiving Antenna with Dual-Capacitive Ends to Improve Upper Hemisphere Efficiency for GNSS Applications - Yongjun Jo; Yang Liu; Longyue Qu (Journal of Electromagnetic Engineering and Science)
This study proposes a novel receiving antenna with higher upper hemisphere efficiency for global navigation satellite systems (GNSS) applications. The proposed novel and new-loop-type antenna consists of a series capacitor for input impedance adjustment and two shunt capacitors for resonant frequency control. The proposed method is based on the excitation of the horizontal mode of the ground plane to improve the upper hemisphere efficiency, thus achieving high-reception performance such as good signal-to-noise ratio and upper hemisphere isotropic sensitivity. The proposed antenna was verified in both simulation and measurement, and a 1.5 dB higher upper hemisphere gain was obtained in measurement than that achieved by a conventional inverted-F antenna in the global positioning system (GPS) L1 band (1,575 MHz).